2017
DOI: 10.1097/qai.0000000000001367
|View full text |Cite|
|
Sign up to set email alerts
|

Integrating HIV and Maternal, Neonatal and Child Health Services in Rural Malawi: An Evaluation of the Implementation Processes and Challenges

Abstract: Despite improvement in staff mentorship scores, many MIPs were not exposed to integrated HIV and Maternal, Neonatal and Child Health services offered through MIP clinics primarily because of clinic scheduling challenges. To improve utilization of integrated MIP clinics, careful design of a delivery approach is needed that is acceptable to clinic staff, addresses local realities, and includes appropriate investment and oversight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Two2,22 studies were conducted in Rwanda and reported on different aspects of the same study. Two50,51 were conducted in Malawi. Six records8,3439 reported on different aspects of the same study that was conducted in Uganda and two studies43,44 were conducted in Nigeria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two2,22 studies were conducted in Rwanda and reported on different aspects of the same study. Two50,51 were conducted in Malawi. Six records8,3439 reported on different aspects of the same study that was conducted in Uganda and two studies43,44 were conducted in Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies reported on the following major approaches to mentoring: mentoring by mobile team,8,3439 twining higher performing institution with lower performing institution,26,45,49 embedded mentor support,30,32 providing mentoring support through e-mails and phone calls,43 visits by a single mobile mentor,51 and within-facility mentorship provided by a focal person, experienced or senior person or a manager 50. The included studies assessed the effectiveness of mentorship interventions in three areas: a) clinical competence and performance, b) managerial competence and performance, and c) laboratory quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Option B+ was integrated into existing maternal, newborn and child health services [3,4], including antenatal and postpartum care, family planning, treatment of sexually transmitted infections, and cervical cancer screening. Within a year, Option B+ had more than doubled the number of HIV-positive pregnant and lactating women on ART [4–6], from 22% to 47%. [6] Malawi Population- based HIV Impact Assessment (MPHIA) estimated an HIV prevalence of 8.7% for pregnant women aged 15–49 years between 2015 and 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The PRIME cluster randomised trial (CRT) was conducted and reported on the basis of Consolidated Standards of Reporting Trials (CONSORT) 2010 statement for cluster randomised trials [18,19]. The trial was performed between May 2013 and August 2016 across 30 healthcare facilities in rural and semirural Malawi (protocol previously outlined) [9,20]. All HIV-infected pregnant mothers in the districts of Salima and Mangochi across the Central and South regions of Malawi, respectively, and their infants on delivery were enrolled in PRIME, with clustering occurring from different health facilities stratified by region.…”
Section: Study Design and Study Sitementioning
confidence: 99%